2022
DOI: 10.1002/dmrr.3585
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes albuminuric and non‐albuminuric phenotypes have different morphological and functional ultrasound features of diabetic kidney disease

Abstract: Aims: Whether different diabetic kidney disease (DKD) phenotypes recognise differences in morphological and vascular properties of the kidney is still unexplored.We evaluated the potential role of kidney ultrasonography in differentiating DKD phenotypes in subjects with type 2 diabetes. Materials and Methods:This is a cross-sectional, single-centre study. Total (TRV) and parenchymal renal volumes (PRV) were calculated by applying the ellipsoid formula for conventional (2D) ultrasonography and with manual segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…This non-invasive diagnostic method allows for real-time visualization of kidney size and conditions. Many previous studies suggested a correlation between an increase in total KV and DKD progression in individuals affected by both T1D and T2D, regardless of the presence of albuminuria [25][26][27]. This could be due to the accumulation of extracellular matrix, glomerular hyper ltration or hypertrophy, chronic in ammation, and brosis leading to kidney enlargement.…”
Section: Introductionmentioning
confidence: 99%
“…This non-invasive diagnostic method allows for real-time visualization of kidney size and conditions. Many previous studies suggested a correlation between an increase in total KV and DKD progression in individuals affected by both T1D and T2D, regardless of the presence of albuminuria [25][26][27]. This could be due to the accumulation of extracellular matrix, glomerular hyper ltration or hypertrophy, chronic in ammation, and brosis leading to kidney enlargement.…”
Section: Introductionmentioning
confidence: 99%